A case of telescoping of bowel during sailing - Gupta, Piyush; B. K. Jani; S. Subramaniam (International Journal of Research in Medical Sciences, 2023)
Intussusceptions as an entity is more common in children than adults in whom it is almost always secondary to some associated pathology. Moreover, the presentation is subacute or chronic in nature and all classical features of intussusceptions are rarely present together that makes the diagnosis more challenging. Here we presented a case of ileo-ileal intussusception in an adult male. Obligation of early diagnosis, initial management is unique in such cases. It also focuses on importance of availability of the imaging facilities in management of acute abdomen so as to assist in timely diagnosis as well as the definitive management of intussusceptions.